Review – Biogas Technology to Treat Bioethanol Vinasse - Iqbal Syaichurrozi (Diponegoro University, 2016)
Bioethanol industries generate by-product that is called vinasse. Vinasse is generated from button product of distillation unit. It has high COD, high TS, high temperature, very low pH and some variety compounds. Because of these contents, vinasse can be discharged directly into the water bodies such as the rivers. Vinasse causes negative impact to environment. Therefore, treatment of vinasse must be done. Vinasse treatment methods that had investigated by some authors are aerobic treatment and anaerobic treatment. Anaerobic treatment is more interesting than aerobic treatment, because it can treat wastewaters that contain high COD and it can produce biogas that can be used as alternative fuels.